If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9x+12=2x+89
We move all terms to the left:
9x+12-(2x+89)=0
We get rid of parentheses
9x-2x-89+12=0
We add all the numbers together, and all the variables
7x-77=0
We move all terms containing x to the left, all other terms to the right
7x=77
x=77/7
x=11
| 3(x+1)-7=29 | | 3x+2+x-3+127=180° | | 8x+16=6x+4 | | (x-1)/2+2=2x-2/3 | | 2(2x+4)-4=-4 | | 2^x-1.6=0 | | -4x+21=5(x-5)+10 | | 2x(x+3)+7=0 | | (t+1)²+(t-8)²=4 | | x+(x+6)=8(x+3) | | 2x²-12x+4=18 | | X-5/7x=11 | | 7x+20=6x | | 7x+8=-4x+52 | | 6x=7x+20 | | 4x+35=2x+43 | | 9/4a+7=16 | | (2x)^5=-55 | | y+100=0 | | .2x=10000 | | c/15=22 | | x+4/x-2=x+1/x | | -18x-18x-12=24 | | b/21=-3 | | (6n+2)(5n-8)=0 | | 68=d/4 | | 7(3w+2)/3=-7 | | -2x=-18-8x | | -0.5y=19.5 | | 15/x=105/28 | | 5/2x+11/3=x/2+5/3 | | -0.9=-0.4k |